2007
DOI: 10.1029/2007gl030592
|View full text |Cite
|
Sign up to set email alerts
|

Sensitivity of typhoon‐induced gravity waves to cumulus parameterizations

Abstract: [1] Sensitivity of typhoon-induced gravity waves to cumulus parameterizations is examined using a mesoscale model (MM5). For this, Typhoon Rusa (2002) is simulated with four cumulus parameterizations (Kain-Fritsch, Grell, Anthes-Kuo, and Betts-Miller schemes) and the characteristics of typhoon-induced gravity waves are compared. The experiments show differences in rainband structure and vertical motion, resulting in different forcing spectra for zonal wavelength and period. As a result, induced stratospheric g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
33
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(35 citation statements)
references
References 15 publications
2
33
0
Order By: Relevance
“…Although the present study used the Eulerian approach, we did not employ thresholds of vertical motion, all magnitudes were considered.Spatial fields of simulated flux at 875 hPa on 1800 UTC 14 September (Figure b) are closely related to the structure of Ingrid (Figure ). Figure a at 100 hPa shows conditions slightly above the tropopause (~16 km), where patterns show some relation to Ingrid's structure but also reveal the effects of gravity waves near the tropopause that are better seen in zoomed views (not shown; Chane Ming et al, ; Kim et al, , ; Kuester et al, ; Pfister et al, ). In summary, the WRF results reveal that upward net vertical flux of water vapor occurs at all model levels, including the UTLS.…”
Section: Resultsmentioning
confidence: 98%
“…Although the present study used the Eulerian approach, we did not employ thresholds of vertical motion, all magnitudes were considered.Spatial fields of simulated flux at 875 hPa on 1800 UTC 14 September (Figure b) are closely related to the structure of Ingrid (Figure ). Figure a at 100 hPa shows conditions slightly above the tropopause (~16 km), where patterns show some relation to Ingrid's structure but also reveal the effects of gravity waves near the tropopause that are better seen in zoomed views (not shown; Chane Ming et al, ; Kim et al, , ; Kuester et al, ; Pfister et al, ). In summary, the WRF results reveal that upward net vertical flux of water vapor occurs at all model levels, including the UTLS.…”
Section: Resultsmentioning
confidence: 98%
“…Since the timing of convection is so important for generating waves, the time differences between the NR and AIRS sampling most likely explain the differences in the summer hemisphere. The convective parametrization could also be important (Kim et al, 2007). Figure 3 shows the July average amplitudes near ∼35 km for AIRS and the NR.…”
Section: Comparison To Airsmentioning
confidence: 99%
“…Among convective sources, Tropical Cyclones stand out as intense, organized events and have been specifically studied for their generation of GWs, both with observations [e.g., Sato , ; Dhaka et al , ] and with numerical simulations [ Kim et al , , ; Kuester et al , ; Kim and Chun , ]. As finer resolution has become available, numerical simulations have stressed the role of waves with shorter and shorter wavelengths: Kim et al [] simulated waves emitted by typhoon Rusa (2002) with a horizontal resolution of Δ x =27 km and found dominant wavelengths of 300–600 km, with periods of 6–11 h. Kuester et al [] simulated Hurricane Humberto (2001) with a resolution down to Δ x =3 km and found dominant wavelengths of 15–300 km, with periods 20–100 min.…”
Section: Introductionmentioning
confidence: 99%